Optimizing position-specific preparation: Long-term pre-match warm-up external load analysis using micro-sensor integrated LPS in elite female volleyball players - Altundag, E.; Cengizel, E.; Akarçesme, C.; Miale, G. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Although it is known that determining the external loads during matches and training is essential for coaches to understand game demands, optimize and specify players` performance, or avoid overtraining or overload scenarios, it has been observed that the pre-match warm-up external load is neglected. The aims of this study were (i) assess the pre-match warm-up external load for female volleyball players and (ii) compare this load by player position.